The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1974
DOI: 10.21273/jashs.99.4.381
|View full text |Cite
|
Sign up to set email alerts
|

The Commercial Implications of Gibberellin A4A7 Plus Benzyladenine for Improving Shape and Yield of ‘Delicious’ Apples1

Abstract: Gibberellin A4A7 (GA4-7) and benzyladenine (BA) were applied to ‘Starkrimson Delicious’ apples from 1969 through 1972. In initial tests, GA4-7 + BA (50 to 200 ppm each) increased fruit length, fruit wt and length/diam ratio (L/D) but did not alter diam or fruit color. Firmness and seed numbers were reduced only at 200 ppm. At concn above 50 ppm flower initiation was substantially reduced. Concentrations of 25 ppm were as effective as 50 ppm but concentrations below 25 ppm were not effective. To be most effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

1979
1979
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 1 publication
0
16
1
Order By: Relevance
“…Fruit weight was increased in the absence of thinning when either GA4 + 7 or B A ^e re applied starting at FB + 11 days but not when used in combination (Table 3). Sprays of GA4 + 7 and BA can increase fruit weight of 'Delicious' primarily by elongation of the calyx end, and maximum response appears to be when applied during the bloom period (23). However, Looney (14) has reported that treatments on 'Spartan' with GA4 + 7 and BA increased the L/D ratio and especially fruit weight for at least 5 weeks after bloom.…”
Section: Discussionmentioning
confidence: 99%
“…Fruit weight was increased in the absence of thinning when either GA4 + 7 or B A ^e re applied starting at FB + 11 days but not when used in combination (Table 3). Sprays of GA4 + 7 and BA can increase fruit weight of 'Delicious' primarily by elongation of the calyx end, and maximum response appears to be when applied during the bloom period (23). However, Looney (14) has reported that treatments on 'Spartan' with GA4 + 7 and BA increased the L/D ratio and especially fruit weight for at least 5 weeks after bloom.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of increased fruit weight following GA4 + 7 + BA application (8,11) were not confirmed here (Tables 2 and 3). This may be due in part to the GA4 + 7 + BA concentrations used in this study, which were generally above those which are recommended commercially.…”
Section: Resultsmentioning
confidence: 58%
“…Also, Miller (8) has reported that geographical location can modify the response to GA4 + 7 + BA. GA4 + 7 + BA increases fruit size in the warmer regions of the United States such as North Carolina (11) and Georgia (8), but confirmation in northern states is lacking. Looney reported that GA4 + 7 + BA increased the size of 'Spartan' apples in British Columbia but the response occurred only when applications were made a week or more after bloom (7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations